SPE Symposium on Improved Oil Recovery 2008
DOI: 10.2118/113417-ms
|View full text |Cite
|
Sign up to set email alerts
|

Residual Oil Saturation from Polymer Floods: Laboratory Measurements and Theoretical Interpretation

Abstract: A detailed analysis of the laboratory corefloods and their simulation matches, carried out earlier in our laboratory, show that, while a tertiary polymer flood cannot mobilize the waterflood residual oil, a secondary polymer flood can displace oil below the waterflood residual oil saturation observed in the same core. We show with a simplified pore-level modeling study that, when a viscoelastic polymer solution surrounds a mobile, funicular oil column in a chain of pores and slowly drains it,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
51
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(54 citation statements)
references
References 31 publications
2
51
0
1
Order By: Relevance
“…Huh and Pope (2008) observed S or reductions ranging from 2 to 22 saturation percentage points using Antolini cores and a constant capillary number of 4x10 -6 . Alaska's North Slope contains a very large unconventional oil resource-over 20 billion barrels of heavy/viscous oil (Stryker et al 1995, Thomas et al 2007).…”
Section: Effect Of Residual Oil Saturation On Recovery Efficiency Durmentioning
confidence: 90%
See 2 more Smart Citations
“…Huh and Pope (2008) observed S or reductions ranging from 2 to 22 saturation percentage points using Antolini cores and a constant capillary number of 4x10 -6 . Alaska's North Slope contains a very large unconventional oil resource-over 20 billion barrels of heavy/viscous oil (Stryker et al 1995, Thomas et al 2007).…”
Section: Effect Of Residual Oil Saturation On Recovery Efficiency Durmentioning
confidence: 90%
“…However, in the less-permeable pathways, polymer flooding could drive the S or to a lower value via the same mechanism mentioned at the end of the previous paragraph. During polymer flooding, Huh and Pope (2008) observed S or reductions (relative to waterflooding) ranging from 2 to 22 saturation percentage points using heterogeneous Antolini cores and a constant capillary number of 4x10 -6 .…”
Section: Previous Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Wang et al [7] had analyzed the changes in micro forces between polymer and residual oil, they studied the elastic properties using mathematical simulation and lab tests, and further understood the mechanism of PF. Huh et al [8] had carried out a detailed study on the residual oil of PF using core flooding tests and simulations and it has been concluded that the PF for the second time could reduce the saturation of residual oil, while a PF for the third time will be useless.…”
Section: Introductionmentioning
confidence: 99%
“…Huh and Pope (2008) provided guidelines for both laboratory work and theoretical interpolation using core experiments and history matching simulations. Their conclusion was that viscoelastic behaviour can reduce the residual saturation when polymer is injected in secondary recovery mode instead of as the traditional tertiary flood.…”
Section: Introductionmentioning
confidence: 99%